Bacterial cell immobilized packed bed reactor for the elimination of dissolved organics from biologically treated post-tanning wastewater and its microbial community profile. (April 2023) - Mannacharaju, Mahesh; Ganesan, Sekaran; Lee, Jung-Kul; Rajagopal, Rajinikanth; Chang, Soon Woong; Ravindran, Balasubramani
Abstract: In conventional, the biologically treated tannery wastewaters are rich in dissolved organics and the application of reverse osmosis (RO) to biologically treated tannery wastewater was challenged with fouling and failure of RO membrane due to existence of lingering dissolved organic compounds. In present investigation the bacterial cell immobilized packed bed reactor (CIPBR) was operated to remove the dissolved organic compounds in biologically treated post-tanning wastewater to avoid membrane fouling in RO. The efficient microbial syndicate to eliminate dissolved organics in post-tanning wastewater was isolated and immobilized on to the carbon silica matrix (CSM) in the range of 2.98 ± 0.2 × 10 7 cells gm −1 of CSM and the same was used as a carrier matrix in the packed bed reactor. The CIPBR established the CODtot, CODdis and BOD removal efficiency by 61 ± 4%, 57 ± 4% and 87 ± 3% respectively with CODtot, CODdis and BOD remained in the treated wastewater as 236 ± 21 mg/L, 228 ± 21 mg/L, and 12 ± 3 mg/L under continuous operation. The removal of dissolved organic compounds from the post-tanning wastewater was confirmed using UV–Visible and FT-IR spectroscopic studies. Among the total microbial community, the phylum Proteobacteria played most abundant role with 48.47% of relative abundance for the removal of dissolved organics in biologically treated post-tanning wastewater. The significance of the study is to replace the tertiary treatment unit operation in the conventional ETP/CETP to remove dissolved organics in wastewater. Graphical abstract: Image 1 Highlights: Bacterial Cell Immobilized Packed Bed Reactor (CIPBR) was designed and fabricated. Removal of dissolved organics was confirmed by UV–Vis & FT-IR studies. The metagenomic analysis was carried out to evaluate the microbial community structures in CIPBR. The phylum proteobacteria showed 48.47% of relative abundance in total microbial community.